Effects of different throttle opening and air intake lengths on the volumetric efficiency of SI engine using 1D simulation method - Ahmad Harazi, Mohamad Firzan; Hairuddin, Abdul Aziz; As’arry, Azizan; Masuri, Siti Ujila (Universiti Putra Malaysia Press, 2024)
Engine performance is influenced by volumetric efficiency, an engine’s ability to put air into its cylinders. It is known for its intake length being tuned based on engine speed due to the air pressure wave behavior. However, the airflow into the intake system is controlled by the throttle opening, so there is a need to study the performance effect of intake length that is tuned based on it. Thus, this current study focuses on the impact of different throttle opening and intake lengths in relation to engine speed on the volumetric efficiency of the Proton CamPro 1.6L SI engine. The simulation runs on different ranges of engine speeds from 1000 rpm to 7000 rpm and different intake lengths with different throttle opening angles. The critical finding of this study revealed that tuning intake length based on throttle opening showed an improvement of 1.3% for volumetric efficiency at the low rpm range. It is by tuning the intake length to 400 mm at a throttle opening of 70° for 1000 rpm and 450 mm intake length with a throttle opening of 50° at 2000 rpm. However, it showed that 90° or wide-open throttle provides the best volumetric efficiency for mid and high-range rpm for all intake lengths. The highest efficiency achieved is 101% at 4000 rpm with a 500 mm length intake and wide-open throttle. The findings from this study contribute to a good understanding of engine performance through intake length tuned based on throttle opening.